Potential of mobile technologies and applications in the detection of mild cognitive impairment among older generation groups. (9th August 2017) - Klimova, Blanka; Valis, Martin; Kuca, Kamil
ABSTRACT: At present, demographic changes result in the growing number of older people. This trend inevitably brings about serious social and economic issues, as well as occurrence of aging diseases. The purpose of this study is to discuss the potential of using mobile technologies and applications in the detection of aging disorders such as mild cognitive impairment. The methods used for this review study include a literature search in the world's acknowledged databases. The findings of this study indicate that mobile applications can serve as appropriate diagnostic tools for aging disorders such as mild cognitive impairment because they seem to provide better, faster, and less costly care for older people.